Princess For A Day - Cocca-Leffler, Maryann; Nang Chan Yeema (New York, USA Grosset & Dunlap Publisher, 1998)
Today Jessica is a princess. She makes a crown. She chooses a dress. She puts on her jewels.
Keywords: Level Books